The role of inflammatory biomarkers in adolescent major depressive disorder: a systematic review - Kwarta, Cityta Putri; Sari, Mike Permata; Suharti; Sundjaya, Tonny; Novitasari, Prihatini Dini; Taufik, Kumar (Berita Kedokteran Masyarakat, 2026)
Purpose: Major Depressive Disorder (MDD) in adolescents is an escalating mental health problem with underlying biological pathways. Increasing evi- dence highlights the role of inflammatory response and immune dysregulation in its development and progression. This study aims to explore the role of inflammatory biomarkers in Major Depressive Disorder (MDD) among adolescent populations, elucidating their potential utility for more effective treatment strategies. Methods: A systematic review was conducted using Ebsco, PubMed, Scopus, Web of Science, and Google Scholar databases. Studies published between 2019 and 2025 that focused on adolescent MDD (aged 10-19 years) and inflammation were included. Study quality was evaluated using the Joanna Briggs Institute (JBI) tool, and narrative analyses were conducted for data synthesis. The PICOS (Population, Intervention, Comparison, Outcome, and Study Design) framework is used to ensure clarity in defining the research question and inclusion criteria. The systematic review was registered in PROSPERO (CRD420251129403). Results: A total of 29 articles met the inclusion criteria for this study. Across the included studies, elevated levels of pro-inflammatory cytokines, particularly inter- leukin-6 (IL-6) and Tumor Necrosis Factor-Alpha (TNF-α), were consistently associated with MDD in adolescents. Dysregulation of the Hypothalamic- Pituitary-Adrenal (HPA) axis and alterations in anti-inflammatory cytokines such as IL-10 were also observed. These biomarkers were linked to changes in stress hormone regulation. Conclusion: Inflammatory biomarkers play a significant role in the pathophysiology of MDD among adolescents, offering promising avenues for early detection and personalised intervention. Integrating biomarker assessment into clinical practice may improve diag- nosis and guide targeted treatments.